2015
DOI: 10.1634/theoncologist.2014-0144
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis on the Impact of Platinum-Based Adjuvant Treatment on the Outcome of Borderline Ovarian Tumors With Invasive Implants

Abstract: Background. Treatment of borderline ovarian tumors (BOTs) remains contentious, and there is no consensus regarding therapy for BOTs with invasive implants (BOTi). The benefits of platinum‐based adjuvant treatment were evaluated in patients with BOTi at primary diagnosis. Methods. The PubMed database was systematically searched for articles using the following terms: ((borderline) OR (low malignant potential) AND (ovarian)) AND ((tumor) OR (cancer)) AND (invasive implants) AND ((follow‐up) OR (survival) OR (tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
3
16
0
1
Order By: Relevance
“…Other studies report no benefits of adjuvant chemotherapy regardless of stage or tumor histology [34, 35]. A meta-analysis revealed no significant effect of adjuvant chemotherapy on survival in BOT patients with invasive implants [36]. Findings reported here are in agreement with these reports: our multivariate model showed adjuvant chemotherapy is not a factor that is significantly associated with PFS.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies report no benefits of adjuvant chemotherapy regardless of stage or tumor histology [34, 35]. A meta-analysis revealed no significant effect of adjuvant chemotherapy on survival in BOT patients with invasive implants [36]. Findings reported here are in agreement with these reports: our multivariate model showed adjuvant chemotherapy is not a factor that is significantly associated with PFS.…”
Section: Discussionsupporting
confidence: 91%
“…According to the available evidence, there is no benefit in adding adjuvant treatment to upfront surgery in patients with sBOTs with invasive implants 111 151–171. A meta-analysis on BOTs concluded that there is no evidence supporting the use of any specific type of adjuvant treatment 153. However, considering the low risk of invasive high-grade relapse, it is unlikely that it will be possible to demonstrate the efficacy of adjuvant treatment in these patients.…”
Section: Resultsmentioning
confidence: 99%
“…The basic treatment for BOT is surgery, while indications for adjuvant treatment seem to be limited with neither randomised studies nor literature reviews having demonstrated the advantage of adjuvant therapy on survival [29,30]. The surgical treatment for BOT is historically based on the treatment of IOC, where the performance of a hysterectomy is justified to diagnose microscopic peritoneal implants on the surface of the uterine serosa.…”
Section: Resultsmentioning
confidence: 99%